2009
DOI: 10.1021/jf803315d
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Red Beetroot against Carbon Tetrachloride- and N-Nitrosodiethylamine-Induced Oxidative Stress in Rats

Abstract: The aim of the study was to investigate the potential protective effect of beetroot juice in a model of oxidative stress induced by N-nitrosodiethylamine (NDEA) and carbon tetrachloride (CCl(4)). Male Wistar rats were treated with beetroot juice per os, 8 mL/kg/day for 28 days, and a single i.p. dose of the xenobiotics: 150 mg/kg NDEA or 2 mL/kg CCl(4). Simultaneously, two groups of rats not pretreated with juice were given only each of the xenobiotics. The level of microsomal lipid peroxidation in the liver, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 29 publications
8
62
2
3
Order By: Relevance
“…The key markers measured in these studies were lipid peroxidation and activity of antioxidant enzymes (catalase, SOD, glutathione peroxidase, and glutathione reductase). Additionally, treatment with red beet juice has also protected leukocyte DNA against damage, suggesting multiple roles for red beet phytochemicals (Kujawska et al 2009 ) .…”
Section: Diabetes-associated Biological Activities Of Red Beet and Itmentioning
confidence: 99%
“…The key markers measured in these studies were lipid peroxidation and activity of antioxidant enzymes (catalase, SOD, glutathione peroxidase, and glutathione reductase). Additionally, treatment with red beet juice has also protected leukocyte DNA against damage, suggesting multiple roles for red beet phytochemicals (Kujawska et al 2009 ) .…”
Section: Diabetes-associated Biological Activities Of Red Beet and Itmentioning
confidence: 99%
“…A number of studies report that beetroot, in the form of a juice supplement, protects against oxidative damage to DNA, lipid and protein structures in vitro (Pietrzkowski et al, 2010;Kujawska et al, 2009;Winkler et al, 2005). A study by Wootton-Beard and Colleagues suggests that a key mechanism by which beetroot juice exerts its antioxidant effects is by scavenging radical species .…”
Section: Introductionmentioning
confidence: 99%
“…While structural similarity does not guarantee similar gene expression responses, literature review does suggest that these compounds should share some common mode of action. For example, all four compounds are metabolized by the cytochrome P450 metabolizing enzyme CYP2E1 and/or alcohol dehydrogenase (ADH) causing oxidative stress which (partially) explains their hepatotoxic effects [47][48][49][50][51][52]. An explanation for the scattered clustering in the meta-analysis could lay in the fact that some essential information in the gene expression metaanalysis may get lost since we found that some compounds did cluster similarly to the protein target z-scores and Tanimoto scores when a distinction was made based on, for example, dose and exposure time (results not shown).…”
Section: Results Of Individual Data Analysis Approachesmentioning
confidence: 99%